Patterns and Strategies of Halal Food Retail Business: A Case Study of Bangkok Metropolitan - Wiriya boonmalert วิริยา บุญมาเลิศ; Bunyaporn phoothong บุณยาพร ภู่ทอง (Dusit Thani College Journal, 2018)
Research on patterns and strategies of Halal food retail business: A case study of Bangkok Metropolitan area Objective 1) To study the patterns and strategies of halal food retail business in the area of Bangkok city 2) To study the marketing strategies of 20 halal food retailers as a group of research sample in the area of Bangkok city. Research finding: 1) Halal food retail business, which consists of cooked food products, fresh food products and Halal branded food products, has different marketing mixes. After analyzing the market, it is found that Halal food retailers are featured in clean products that reach out broadly to target customers because they know and understand consumer behavior and the stores are located in a community with Muslim customers. However, the product range is not yet diversified. It also needs to be developed in terms of nutrition, taste and packaging in order to upgrade the products to a wider market. 2) Study of marketing strategies of Halal food retailers by analyzing STP to gain information in marketing planning. It is found that Halal product market is divided into three groups: community customer, general customer and specific customer. The targeting and market positioning are different. For community customers, their product prices are relatively cheap. For general customers, the prices are set based on market price. And for specific customers, the prices will be set higher because of its niche and sensitive market characteristics which leads to a risk that people will not buy it.